Peran Internet dalam Penggunaan Media Sosial terhadap Siswa - Siswi SB At-Tanzil Hicom Malaysia - Sufi, Muhammad Sufi Ali Imran; Firdaus, Firdaus; Hartono, Djoko Setyo; Nofikasari, Nofikasari (Jurnal PKM Manajemen Bisnis, 2025)
The implementation of this activity is based on the lack of internet-related education in the use of social media for SB At Tanzil Hicom students. The purpose of implementing this educational activity is so that these students know and understand the positive and negative impacts of the internet and how to maximize an application or website. For the methods I used in implementing this educational activity, namely qualitative methods, lectures, and practices. I conducted data searches through cellphone tools which I then conveyed to them with simpler language and analogies for easy understanding. The results of the implementation of these activities are that students are able to understand the use of the internet properly and also understand its positive and negative impacts. It is hoped that in the future they will be able to better utilize the role of the internet in the use of social media.